Aceclofenac-loaded chondroitin sulfate conjugated SLNs for effective management of osteoarthritis. (November 2014) - Bishnoi, Mamta; Jain, Ankit; Hurkat, Pooja; Jain, Sanjay K.
Abstract Background: In intra-articular drug delivery, there are number of shortcomings such as lymphatic drainage from the synovial cavity, frequent dosing, adverse side effects and patient discomfort in the management of osteoarthritis (OA). Purpose: This research work reports the development and characterization of aceclofenac-loaded chondroitin sulfate (CS) conjugated (CS-SLN) and unconjugated solid lipid nanoparticles (SLN) for the effective management of OA. Methods: The SLNs were prepared using modified solvent injection method and coupled with CS. They were further characterized for size and size distribution, zeta potential, surface morphology, % entrapment efficiency and in vitro drug release profile. Anti-inflammatory activity and in vivo performance was also predicted. Results: The particle size of the SLN and CS-SLN was found to be 143.4 ± 0.9 nm and 154.2 ± 1.1 nm, respectively. SLNs exhibited sustained drug release (SLN, 64.25 ± 0.75%; CS-SLN, 57.82 ± 0.62%) in vitro for more than 24 h. In vivo performance studies revealed the highest uptake of SLNs by the knee joint. Discussion: SLNs enhanced accumulation at the knee joint due to specific interactions with CD44, annexin and leptin receptors attributed to CS coupling. Conclusion: CS-SLN could be potentially effective vector for the treatment or management of OA.